Parity-nonconservation effects on the radiative recombination of heavy hydrogenlike ions - Gunst, Jonas Friedrich; Surzhykov, Andrey; Artemyev, Anton; Tashenov, Stanislav (Physical review. A, Atomic, molecular, and optical physics, 2013)
Based on the theoretical analysis of the radiative recombination of heavy hydrogen-like ions with unpolarized electrons, a scheme is proposed for observing atomic parity nonconservation (PNC). The scheme employs the sensitivity of the polarization properties of recombination photons on the PNC-induced mixing of opposite-parity ionic levels. For the electron capture into the 1s2p3P0 state of helium-like ions, in particular, the PNC leads to a rotation of the photon linear polarization on the angle, directly proportional to the 1s2p3P0-1s2s1S0 mixing parameter. Owing to the recent advances in the development of x-ray polarimeters, the observation of such a rotation angle and, hence, the corresponding parity mixing is likely to become feasible in the future.
Gesehen am 10.02.2021